2012
DOI: 10.1111/j.1440-1681.2011.05649.x
|View full text |Cite
|
Sign up to set email alerts
|

Early origins of heart disease: Low birth weight and determinants of cardiomyocyte endowment

Abstract: 1. World-wide epidemiological and experimental animal studies demonstrate that adversity in fetal life, resulting in intrauterine growth restriction, programmes the offspring for a greater susceptibility to ischaemic heart disease and heart failure in adult life. 2. After cardiogenesis, cardiomyocyte endowment is determined by a range of hormones and signalling pathways that regulate cardiomyocyte proliferation, apoptosis and the timing of multinucleation/terminal differentiation. 3. The small fetus may have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 129 publications
(176 reference statements)
0
76
1
Order By: Relevance
“…17 Because fetuses have several mechanisms to compensate for undernutrition, intrauterine hypoxia is strongly associated with fetal growth in utero. 18 Previous experimental studies have demonstrated that models of chronic embryonic hypoxia can lead to FGR, cardiac chamber dilatation, reduced cardiac systolic and diastolic dysfunction and increased IMT; these changes persist into adulthood, 7,19 as does increased cardiac vulnerability to ischemia. 20 The molecular mechanism of fetal heart programming is unknown, but recent experimental studies have shown a possible mechanism in hypoxia-induced IUGR animal models.…”
Section: Systolic Functionmentioning
confidence: 99%
“…17 Because fetuses have several mechanisms to compensate for undernutrition, intrauterine hypoxia is strongly associated with fetal growth in utero. 18 Previous experimental studies have demonstrated that models of chronic embryonic hypoxia can lead to FGR, cardiac chamber dilatation, reduced cardiac systolic and diastolic dysfunction and increased IMT; these changes persist into adulthood, 7,19 as does increased cardiac vulnerability to ischemia. 20 The molecular mechanism of fetal heart programming is unknown, but recent experimental studies have shown a possible mechanism in hypoxia-induced IUGR animal models.…”
Section: Systolic Functionmentioning
confidence: 99%
“…49 The adult mammalian heart contains binucleated cardiomyocytes, although the degree of binucleation varies among species. 50 For example, most adult murine cardiomyocytes are binucleated, whereas binucleation of human cardiomyocyte remains at a constant low level throughout life. 25 It has been shown Figure. Recent strategies for cardiomyocyte regeneration.…”
Section: Animal Models Of Cardiac Regenerationmentioning
confidence: 99%
“…Postnatal hyperoxia exposure (Hx) in neonatal rodents is frequently used to mimic chronic lung disease of prematurity, also known as bronchopulmonary dysplasia (11). Importantly, the rodent heart is also relatively premature at the time of birth, suggesting that this model may be appropriate to mimic the effects of prematurity on the heart as well (12). Brief neonatal oxygen exposure in mice was previously associated with increased RV hypertrophy, reduced pulmonary microvasculature, and premature death in adulthood (13).…”
mentioning
confidence: 99%